2021
DOI: 10.1016/j.xfss.2021.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the TMRW vapor phase cryostorage platform using reproductive specimens and in vitro extended human embryo culture

Abstract: Objective: To assess the impact of shipment and storage of sperm, oocytes, and blastocysts in vapor phase nitrogen compared with static storage in liquid phase nitrogen. Design: Prospective cohort-matched study. Setting: Multiple in vitro fertilization laboratories in an in vitro fertilization network. Patient(s): Fifty-eight human embryos, 32 human oocytes, 15 units of bovine semen. Intervention(s): Vapor vs. liquid nitrogen. Main Outcome Measure(s): The postwarming survival of oocytes, sperm, and blastocysts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This device is similar to the Cryotop device, differing in the possession of a porous Evaluation of the data TMRW showed that this system does not have any deleterious effects on the survival rate of sperm, oocytes, and blastocysts. In addition, the storage of embryos in the TMRW vapor phase platform did not have any impact on the post-developmental potential of human blastocysts (72). Modern high-efficiency vapor phase tanks, such as the Chart MVE 1500, allow the storage of specimens in the vapor phase at temperatures below −150 • C (73).…”
Section: Oocytes and Embryosmentioning
confidence: 99%
“…This device is similar to the Cryotop device, differing in the possession of a porous Evaluation of the data TMRW showed that this system does not have any deleterious effects on the survival rate of sperm, oocytes, and blastocysts. In addition, the storage of embryos in the TMRW vapor phase platform did not have any impact on the post-developmental potential of human blastocysts (72). Modern high-efficiency vapor phase tanks, such as the Chart MVE 1500, allow the storage of specimens in the vapor phase at temperatures below −150 • C (73).…”
Section: Oocytes and Embryosmentioning
confidence: 99%